#MIGRAINE-TOO News et fake news sur une maladie invisible - Schoenen, Auteur:Jean (Presses universitaires de Liège, 2022)
Migraine affects 25% of the population and is the 2nd most incapacitating disease in women between the ages of 25 and 50, according to studies by the World Health Organization. It is multiple and complex in its clinical expression as well as in its causes and treatments. Add to this the fact that it is not visible on clinical examination or brain scan, and you will understand why it can suffer from a triple distortion of perception: 1) perceived by the patient's entourage as a "non-disease" not deserving of any interest; 2) perceived by the patient as a fatality with no real effective treatment; 3) perceived by all as a mysterious disease about which a host of misconceptions (fake news) are circulating In this book, I try to separate the wheat from the chaff among the information circulating on migraine, based on 40 years of clinical experience and research at the University of Liege. I hope to show migraine sufferers that their migraine is not a fatality, but a neurological disease where research progress in recent decades has paved the way to increasingly effective treatments. To do so, I will illustrate my remarks with scientific data, sometimes specialized, because I believe that migraine sufferers will understand them if they are presented clearly and illustrated (106 figures and tables), and that it is in their interest to know them in order to be able to form their personal opinion with full knowledge of the facts. This book will therefore also be useful for caregivers of migraine sufferers. I also hope to convince non-migraine sufferers from all walks of life that this is a disabling disease, which, although not lethal, kills the quality of life and can undermine a life, a couple or a professional career. Like other diseases, it deserves the interest of relatives, employers, academics and policy makers.